2021
DOI: 10.1073/pnas.2024202118
|View full text |Cite
|
Sign up to set email alerts
|

The ORF8 protein of SARS-CoV-2 mediates immune evasion through down-regulating MHC-Ι

Abstract: COVID-19, caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), has become a global pandemic and has claimed over 2 million lives worldwide. Although the genetic sequences of SARS-CoV and SARS-CoV-2 have high homology, the clinical and pathological characteristics of COVID-19 differ significantly from those of SARS. How and whether SARS-CoV-2 evades (cellular) immune surveillance requires further elucidation. In this study, we show that SARS-CoV-2 infection leads to major histocompability com… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

17
368
6
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 360 publications
(393 citation statements)
references
References 61 publications
17
368
6
2
Order By: Relevance
“…Even the double-mutant V62L/L84S did not significantly affect its binding with IRF3. Our results are in line with the previous studies in which L84S substitution did not enhance the IFNß antagonism and the downregulation of MHC-I compared to ORF8 WT (Rashid et al, 2021;Zhang et al, 2021). We have found that the nuclear translocations of IRF3 by either overexpressing ORF8 WT or L84S in HEK293T cells were the same (Rashid et al, 2021).…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…Even the double-mutant V62L/L84S did not significantly affect its binding with IRF3. Our results are in line with the previous studies in which L84S substitution did not enhance the IFNß antagonism and the downregulation of MHC-I compared to ORF8 WT (Rashid et al, 2021;Zhang et al, 2021). We have found that the nuclear translocations of IRF3 by either overexpressing ORF8 WT or L84S in HEK293T cells were the same (Rashid et al, 2021).…”
Section: Discussionsupporting
confidence: 93%
“…So far, these mutations occurred in structural, non-structural, and accessory proteins of SARS-CoV-2 (Nagy et al, 2021). The accessory protein, i.e., the ORF8 protein sequence of SARS-CoV-2, has the least homology with that of SARS-CoV (Zhang et al, 2021). In the current study, we adapted structural and biophysical analysis approaches to explore the impact of various mutations of ORF8, such as S24L, W45L, V62L, and L84S, on its ability to bind IRF3 and to evade the host immune system.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations